If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2x + -4) = 15 Reorder the terms: 5 + -1(-4 + 2x) = 15 5 + (-4 * -1 + 2x * -1) = 15 5 + (4 + -2x) = 15 Combine like terms: 5 + 4 = 9 9 + -2x = 15 Solving 9 + -2x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2x = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 15 + -9 -2x = 15 + -9 Combine like terms: 15 + -9 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| 4x-16x-9=0 | | 2/3+(1/3)= | | -2x+(-6)=28 | | 12+5x=0 | | N/80=4/32 | | 3x^2+132x+180=0 | | x^2+44x+60=0 | | 3x+6(x+3)=72 | | x+10+2x-5+x+10=90 | | 4x+122=11x-11 | | 26z+37z=315 | | 0.04x+0.07(5000-x)=300.00 | | 2x+7x-4=-22 | | 5*ln(x)=0.5 | | -14s+8s=126 | | y=log(1/9) | | 3x^2=132x+180 | | 45.03+z=271.35 | | 12a^3+6a^2-18=0 | | 2x^2-lnx=0 | | 5*ln(x)/x^2 | | 4(x+4)[8]=3x-3 | | x+4x-15+x=90 | | y=x^3+6x^2+12x | | 8(m+6)+7m= | | 2n/3-5/13=63/39 | | 15-6x=6-9x | | 28x=8 | | 19=11-8a | | 2(-x-2)=-4(3x+6) | | 6x/5-5=13 | | 34-6x=-588x |